Changes in dietary intake during Ramadan month among university students in Bangladesh: a cross-sectional study - Mohammad Delwer Hossain Hawlader; Koustuv Dalal; Md. Kamrul Hasan; Humayun Kabir; Somayea Sultana Mim; Lamisa Rahman; Miah Mohammad Akiful Haque; Mamunur Rahman; Moez AlIslam E. Faris; Sahabi Kabir Sulaiman; Fatimah Isma’il Tsiga-Ahmed; Syed Fahad Javaid; et al. (Discover Food)
Abstract Background Muslims who fast during Ramadan abstain from drinking and eating from dawn to sunset, which has major dietary, lifestyle, and metabolic implications. Due to their active schedule, university students are among the most affected groups by the observance of Ramadan fasting. The study investigated changes in the perceived amounts of dietary intake during Ramadan and the factors associated with these changes among Bangladeshi Muslim university students. Methods A cross-sectional study was conducted using a semi-structured questionnaire during the month of Ramadan in the year 2021 (10 May 2021 to 10 June 2021). The data were collected online via Google forms following snowball sampling and convenience sampling principles. The Pearson chi-square test was performed to determine the associations between independent variables (e.g., age, sex, residence, education level, living status) and the dependent variables (e.g., perceived change of carbohydrate-related foods, protein-related foods, oils, whole milk, Ramadan occasion-related foods, and others). Results A total of 867 university students were recruited; 66% of them were males. The intake of cereals was significantly higher among males than females (12.22% vs. 8.16%, p = 0.001). The vegetable intake was significantly lower among students with hypertension (3.51% vs. 11.98%, p < 0.001) and diabetes (9.43% vs. 11.70%, p < 0.001). The consumption of homemade dishes was significantly higher among students living with their families (47.30% vs. 5.66%, p < 0.001). Conclusion The study revealed different changes in perceived dietary intakes and associated factors among university students during Ramadan. Our research calls on policymakers and public health experts to create health education programs and public health awareness campaigns to impart healthy eating behaviors during Ramadan.